Environmental exposure to benzene, micronucleus formation and polymorphisms in DNA-repair genes: a pilot study - Angelini, Sabrina; Lorenzo Bermejo, Justo (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2012)
This report is part of a biomarker study conducted in an Italian population with exposure to environmental benzene ranging from 1.43 to 31.41 μg/m³ (values from personal sampling). DNA damage induced by benzene is the crucial mechanism of its genotoxicity, which leads to chronic benzene poisoning, haematotoxicity and leukaemia. Therefore, genetic variation in DNA-repair genes may modulate susceptibility to benzene-induced DNA damage. In light of this, the effects of polymorphisms in DNA-repair genes (APEX1, hOGG1, NBS1, XPD, XRCC1, and XRCC3) on micronucleus (MN) formation as a biomarker of early biological effects were evaluated. A significantly higher median MN frequency was recorded in traffic wardens than in controls. However, none of the analysed polymorphisms was significantly associated with the median MN frequency. A gene-gender interaction was observed for the APEX1 genotype. The APEX1 variant genotype was associated with significantly lower median MN frequency in men, not in women. Statistical analysis did not reveal any association between the score of the protective alleles - hypothetically pushing the pathway towards optimal DNA-damage repair - and MN. Even though there are some limitations in the study, our results indicate that the general population may be exposed to benzene concentrations higher than the threshold level for air-quality standards in the European Union of 10 μg/m³. Furthermore, urban traffic wardens are exposed to significantly higher levels of benzene than individuals spending most of the time indoors. This higher exposure may contribute to DNA damage, suggesting that benzene might be implicated both as an environmental and occupational risk factor in leukaemia and other haematological diseases. In conclusion, this study suggest the need for (i) regular monitoring of traffic wardens for possible exposure to benzene, as a precautionary step to reduce the associated health risks, and (ii) more comprehensive studies in order to better elucidate the involvement of APEX1 genotypes in benzene genotoxicity.
Available online 11 January 2012
Gesehen am 13.06.2018